Chapter 3.6 The Influence of RMA Associations on Identity and Policymaking Internationally - Virág Zsár (Emerald Publishing Limited, 2023)
Professional associations mark an important step in the development of any profession. Research Management and Administration (RMA) as a profession is still emerging across Europe, thus the relevance of RMA associations is pertinent. These associations operate either specifically at the transnational or international levels or have certain activities linked to both levels. The theory of social constructivism from the field of international relations will be applied in this analysis with a goal to add additional insights on the topic. The results confirm that RMA associations have an outstanding role in enforcing the internationalised culture of their members, however, members in return can also exert influence on their association. Members are also aware that the association is providing a platform for collective actions in policymaking at national, transnational, and international levels. However, time plays a crucial role in social learning for identity and interest formation, as well as in recognizing the role of RMA associations in corporate agency.
10.1108/978-1-80382-701-820231024; 10.1108/978-1-80382-701-820231024; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262